Molotov, Malenkov, Kaganovich, 1957 : stenogramma iiunskogo plenuma TSK KPSS i drugie dokumenty - sostaviteli : N. Kovaleva, A. Korotkov, S. Mel'chin... et al.. (Mezhdunarodnyi Fond "Demokratiia", 1998)
Includes index.